Social Marketing in Social Media: Investigating the Precursor in Influencing Behaviors of Government Healthcare Campaign - Hadiansyah, Laksmi Saraswati; Nasution, Reza Ashari (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2023)
Abstract. Social media platforms have become a tool for spreading information in society, it enables the government to use this media for giving information to the public, especially in pandemic situations. Social media has revolutionized the way of reaching out to consumers and communicating with them. Branding in social media strategy is commonly used in advertising and product marketing but has not been widely used in the health communication field. In this study, we shine a light on the new way health communications marketing is reaching audiences with health messages. The information adoption process in social media might be a strategy for spreading trusted information on the internet, so this study aims to examine the precursor of this case. Using Structural Equation Model (SEM) we identify the relationship between variables influencing certain behaviors related to health content in social media. This study used snowballing technique for collecting data through online questionnaires with a sample of 297 respondents who were in accordance with the criteria of the population. We offer insight for future research on these topics by discussing the public marketing role in social media interaction. Our outcome of the study to serve as a platform to positively impact future research on information in social media regarding health is being delivered to society. Furthermore, the study may develop a socialization program to educate society, campaign for a healthy lifestyle, and health information media using social media. Keywords: Social marketing, social media, information adoption, sharing behavior, cet framework. Abstrak. Platform media sosial telah menjadi salah satu alat penyebaran informasi di masyarakat, sehingga pemerintah dapat memanfaatkan media tersebut untuk memberikan informasi kepada masyarakat, terutama dalam situasi pandemi. Media sosial telah merevolusi cara menjangkau konsumen dan berkomunikasi dengan mereka. Branding dalam strategi media sosial biasa digunakan dalam periklanan dan pemasaran produk namun belum banyak digunakan dalam bidang komunikasi kesehatan. Dalam studi ini, kami menyoroti cara baru pemasaran komunikasi kesehatan dalam menjangkau khalayak dengan pesan kesehatan. Proses adopsi informasi di media sosial dapat menjadi strategi penyebaran informasi terpercaya di internet, sehingga kami meneliti prekursor pada kasus ini. Dengan menggunakan Structural Equation Model (SEM) kami mengidentifikasi hubungan antara variabel yang mempengaruhi perilaku tertentu terkait konten kesehatan di media sosial. Penelitian ini menggunakan teknik pengumpulan data snowballing melalui kuesioner online dengan sampel 297 responden yang sesuai dengan kriteria populasi. Kami menawarkan wawasan untuk penelitian masa depan mengenai topik ini dengan mendiskusikan peran pemasaran publik dalam interaksi media sosial. Hasil penelitian kami berfungsi sebagai platform untuk mengedepankan penelitian di masa depan mengenai informasi di media sosial mengenai kesehatan yang disampaikan kepada masyarakat. Selanjutnya penelitian ini dapat mengembangkan program sosialisasi untuk mengedukasi masyarakat, mengkampanyekan pola hidup sehat, dan media informasi kesehatan melalui media sosial. Kata kunci: Social marketing, social media, information adoption, sharing behavior, cet framework